Синтез наноструктур з кристалічного оксиду цинку - Gorbyk, P. P.; Dubrovin, I. V.; Demchenko, Yu. O.; Kashun, G. M.; Lytvyn, Yu. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
A method of synthesis of nanosized structures and whiskers of zinc oxide tetrahedral crystals has been developed. Synthesis has been carried out in a gas flow and nanosized gold particles have been used as catalyst particles that determine a required density of crystallizing nuclei on single crystal silicon substrates. The synthesized whisker and tetrahedral structures have been studied by X-ray phase analysis, scanning electron microscopy, Auger-electron spectroscopy, and atomic force microscopy. According to the results of these studies, the fabricated structures have composition of pure zinc oxide, low defect density, hexagonal wurtzite structure, a typical thickness in the range of 50–300 nm, and lengths of up to 40 mm. The synthesized structure are very promising for various applications in the fields of microelectronics, optoelectronics, biomedicine and others.